Atlas da Região de Carajás: uma introdução - Eudes Leopoldo; Maurílio de Abreu Monteiro; Abraão Mascarenhas; Maria Rita Vidal; Hervé Théry (Confins)
The proposal for an Atlas of the Carajás Region is a product of the research project “Production of subsidies for the formulation of public policies for the Carajás Region”. The objective is to produce an atlas with various cartographic products, which allows spatializing the main elements and relations of production in the Carajás Region. The aim is to provide subsidies for the production of public policies converging with the concrete regional reality, as well as serving as a platform for social and collective movements to have a more appropriate knowledge of their territory of struggles and resistance, thus opening the horizons of new possible and impossible worlds.